2011
DOI: 10.3109/02652048.2010.535620
|View full text |Cite
|
Sign up to set email alerts
|

Spray dried microparticles for controlled delivery of mupirocin calcium: Process–tailored modulation of drug release

Abstract: Spray dried microparticles containing mupirocin calcium were designed as acrylic matrix carriers with modulated drug release for efficient local drug delivery at minimum daily dose. Particle generation in spray drying and its effect on release performance were assessed by varying drug : polymer ratios with consequently altered initial saturations. Narrow-sized microparticles with mean diameters of 1.7-2.5 µm were obtained. Properties of the generated solid dispersions were examined by X-ray, thermal (thermogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…This suggested that the nitro group of nifedipine might form a hydrogen bond with the OH of Soluplus®. The upward shifts of peak positions on decreasing the drug loading resulted from a change in the micro-environment of nifedipine and suggested weaker drug-polymer interactions compared to drug-drug interactions (12,23,37). There was no significant change in nifedipine peak position over the spectral region of aromatic hydrocarbon between 775 and 850 cm −1 (data not shown).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…This suggested that the nitro group of nifedipine might form a hydrogen bond with the OH of Soluplus®. The upward shifts of peak positions on decreasing the drug loading resulted from a change in the micro-environment of nifedipine and suggested weaker drug-polymer interactions compared to drug-drug interactions (12,23,37). There was no significant change in nifedipine peak position over the spectral region of aromatic hydrocarbon between 775 and 850 cm −1 (data not shown).…”
Section: Discussionmentioning
confidence: 98%
“…The presence of a single peak indicates a molecular dispersion of the drug and suggests the presence of a drug-polymer interaction. A shift in a drug related peak position to lower wavenumber indicates stronger drugpolymer interaction than drug-drug interaction and vice versa (23). The stronger drug-polymer interaction results in a weakening of drug-drug interactions, causing a shift to lower frequency.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Topical particulate delivery systems are an advanced form of topical powders. Various release methods have been reported for this type of delivery system: for example methods with paddle or basket apparatus or other similar setups where the sample is added into a container with medium (Alhalaweh et al, 2009;Dürrigl et al, 2011a;Scalia and Mezzena, 2009), flow through cell methods (Salama et al, 2008), dialysis bag methods (Moebus et al, 2012) and methods with Franz cell (vertical diffusion cell) or its modifications (Martinac et al, 2005;Moebus et al, 2012;Salama et al, 2008).…”
Section: Introductionmentioning
confidence: 99%